Olfactory mucosa-mesenchymal stem cells with overexpressed Nrf2 modulate angiogenesis and exert anti-inflammation effect in an in vitro traumatic brain injury model - Zigui Chen; Chunyuan Zhang; Yuhua Fang; He Zhang; Jiawei Luo; Changfeng Miao; Jiale Li; Jun Peng; Yingqi Qiu; Ying Xia; Qisheng Luo (European Journal of Medical Research)
Abstract Background Traumatic brain injury (TBI) is a major cause of disability and mortality among children and adults in developed countries. Transcription factor nuclear factor erythroid-derived 2-like 2 (Nrf2) has antioxidant, anti-inflammatory and neuroprotective effects and is closely related to TBI. Olfactory mucosa-mesenchymal stem cells (OM-MSCs) could promote neural regeneration. At present, the effects of OM-MSCs with overexpressed Nrf2 in brain diseases remain to be explored. Methods The OM-MSCs were prepared and transfected with Nrf2 overexpression plasmid. Those transfected cells were termed as OM-MSCs with Nrf2 overexpression (OM-MSCsNrf2) and co-cultured with rat pheochromocytoma cells PC12 or murine microglia BV2. The effects of OM-MSCsNrf2 on the survival and angiogenesis of PC12 cells were evaluated through cell counting kit-8 (CCK-8) and tube formation assay, and extracellular acidification rate (ECAR) and oxygen consumption rate (OCR) were calculated to reflect glycolysis. Immunofluorescence assay was applied to determine the effects of OM-MSCsNrf2 on microglial polarization, and the underlying molecular mechanisms were analyzed based on the quantification tests of RT-qPCR and immunoblotting. Results Co-culture of OM-MSCsNrf2 and PC12 cells increased the levels of anti-inflammatory cytokines and pro-angiogenesis factors, enhanced the cell survival and angiogenesis. Moreover, we also observed elevated phosphorylation of PI3K/AKT and suppressed BAX protein expression. Meanwhile, OM-MSCsNrf2 inhibited the levels of pro-inflammatory genes and affected the glycolysis in PC12 cells. In the co-cultured system of OM-MSCsNrf2 and BV2 cells, M2 microglial polarization was observed, and the levels of M2 microglia-relevant genes and the phosphorylation of STAT6/AMPKα/SMAD3 were elevated. Conclusion This study proved the effects of OM-MSCsNrf2 on modulating PC12 and BV2 cells in vitro, which, however, necessitates further in vivo validation.